A Study of Hydro-Physical Properties and Characterization of Infiltration into the Surface Layer of Soil at Snoubar Jableh Site–Lattakia - AL-Ali, Yusuf (Latakia University Journal -Biological Sciences Series, 2013)
The process of water infiltration into soil provides the soil and groundwater with water. It also affects runoff formation and soil loss. When the soil of a site is homogeneous, the infiltration characteristics of its surface layer depend on the vegetation cover and human activity. The purpose of this study is to determine the hydro-physical properties which affect infiltration into the soil surface layer at Snoubar Jableh Plantation Site (Lattakia). This is in order to illustrate the impact of vegetal cover and human activity on infiltration characteristics of soil. For this purpose, 20 field infiltration experiments using a single ring were conducted on patches of coniferous and broad-leaved trees. The results indicate that the soil has good infiltration characteristics, except in the oak plot which showed low Ks in comparison with other species plots due to soil compaction and human activity. The results also indicate that the decomposed organic material layer under conifers protect soil against compacting and improve infiltration characteristics.